THE INFLUENCE OF SOCIAL MEDIA AND DIGITAL TECHNOLOGY ON HEALTH PROMOTION IN REDUCING THE PREVALENCE OF INFECTIOUS DISEASES IN URBAN AND RURAL COMMUNITIES IN BIMA REGENCY (Proceedings OPTIMAL, 2025)
This study explores the influence of social media and digital technology on health promotion activities aimed at reducing the prevalence of infectious diseases in both urban and rural communities in Bima City and Regency. The study employed a mixed-methods design, comprising a quantitative survey of 400 respondents (200 from urban areas and 200 from rural areas) and in-depth interviews with 24 key informants. The digital health promotion intervention consisted of educational content disseminated via social media platforms (Facebook and Instagram), community WhatsApp groups, and short message service (SMS/IVR) over a period of six months. Results indicated an increase in the average health knowledge score from 55.2 (SD = 12.4) to 78.6 (SD = 10.1) (p < 0.001). The prevalence of infectious diseases decreased from 10.0% to 6.1% post-intervention, reflecting a relative decrease of 39%. Exposure to digital interventions was significantly associated with a reduced risk of infectious diseases (OR = 0.62; 95% CI: 0.45–0.85; p = 0.003). Qualitative analysis identified the following themes: (1) digital access and literacy; (2) trust in information sources; (3) the role of community leaders; and (4) adaptation of local language content. Conclusion: Digital-based health promotion is effective in reducing the prevalence of infectious diseases, with the caveat that strategies to bridge the digital divide in rural areas are necessary (1, 2, 4). The novelty of this study lies in its provision of community-level empirical evidence that a digital-based multi-channel intervention package, when combined with local strategies (such as engaging community leaders, using local language, and integrating offline methods), not only increases knowledge but also measurably reduces the prevalence of infectious diseases in practice. Recommendations: Strengthening digital literacy capacity, collaborating with local leaders, and utilising offline channels to reach marginalised groups are essential steps forward.